Age-related haematological changes in Murrah buffalo (Bubalus bubalis) calves - H, MOHAN N; NIYOGI, DEBASISH; WAGHAYE, J Y; SINGH, H N (The Indian Journal of Animal Sciences, 2011)
The present study was conducted to assess haematological changes in Murrah buffalo calves (Bubalus bubalis). The haematological analysis was conducted in female calves (n=7/group) and the animals aged 30±3, 60±2, 90±2, 120±2, 150±3, 180±3, 210±3, 240±2, 270±2, 300±2, 330±2 and 360±4 days formed groups 1 to 12 respectively. The red blood cell count, hemoglobin and packed cell volume decreased with age. The changes in erythrocytic indices with respect to age were nonsignificant. The total leukocyte count did not vary among the various age groups but significant changes were observed in the differential leukocyte count. The granulocyte: granulocyte ratio steadily declined from 2.03:1 at 1 month of age to 0.48:1 by 12th month of age. Our results indicated significant hematological changes in the buffalo calves with advancement of age, which may be due to increased physiological destruction of red blood cells, maturational changes of lymphoid organs or environment induced adaptive changes with increasing age.